Iron Age landscape in the Tanuf District, Ad-Dākhliyyah Governorate: A transmountain hypothesis based on surveys and excavations in 2017–2023 - Kuronuma, Taichi; Miki, Takehiro; Tanabe, Kantaro; Kondo, Yasuhisa (The Journal of Oman Studies, 2025)
The Iron Age in Oman is characterised by socioeconomic transformations, including the emergence of regional centres, the revitalisation of sedentary agriculture, and the aflāj water-supply system. Compared to the alluvial basins and oases at the fringes of the inner desert, the sociocultural characteristics of the canyons of the Al Hajar Mountains remain to be explored. Based on the results of our archaeological investigation in the Tanuf District from 2017 to 2023, we demonstrate the transformation of archaeological landscapes in Al Jabal Al Akhdar and along the Wadi Al Abyad in Ad-Dākhliyyah Governorate. In the survey area, we documented 11 Iron Age sites, including cemeteries, occupations, and possible fortifications. These findings reveal the dichotomous Iron Age landscapes in the Tanuf District. The landscape of the canyon of Wadi Tanuf, where temporal occupation was evidenced in a cave, was oriented toward mobility. In contrast, the floodplain areas in Wadi Al Abyad are characterised by an oasis-based sedentary agricultural landscape. A comparative study of the Al Jabal Al Akhdar and Nizwa areas revealed that the spatio-temporarily transitional landscape of the Tanuf District bridges the up- and downstream areas, and the intermediate canyons might have been used as transportation route connecting Al Jabal Al Akhdar and the lower basin.